Effect of double-pass superfluorescence on an erbium doped fibre amplifier - Mahdi, M. A.; S.Thirumeni; P.Poopalan; S. Selvakennedy; Mahmad Adikan H. Ahmad, R. (Universiti Kebangsaan Malaysia, 2001)
Effect of double-pass superfluorescence that clamps a population inversion of the fibre amplifier to have a fixed gain is presented. All optical gainclamping in an erbium doped fibre amplifier is demonstrated using a broadband fibre Bragg grating that reflects the amplified spontaneous emission centred at 1530 nm with a 14 nm bandwidth. The proposed amplifier has an input dynamic range of -5 dBm in order to maintain the gain-clamping effect. Experiments on an eight-channel wavelength division multiplexing system shows that gain clamped at 21 dB. Gain flatness is less than 0.6 dB across all channels and gain variation is about 0.2 dB over the input signal power range.